Deep Roots of Fiscal Behavior - Serhan Cevik; Katerina Teksoz (Journal of Banking and Financial Economics)
This paper investigates the determinants of fiscal policy behavior and its time-varying volatility, using panel data for a broad set of advanced and emerging market economies during the period 1990–2012. The empirical results show that discretionary fiscal policy is influenced by policy inertia, the level of public debt, and the output gap in both advanced and emerging-market economies. In addition, the paper finds that macro-financial factors (such as real exchange rate, financial development, interest rates, asset prices, and natural resource rents) and demographic and institutional factors (such as the old-age dependency ratio, the quality of institutions, and policy anchors such as fiscal rules and IMF-supported stabilization programs) tend to have a significant effect on fiscal policy behavior. The results also indicate that higher government debt leads to more volatile fiscal behavior, while fiscal rules and higher institutional quality reduce the volatility of fiscal policy over time.